Assumptions and Limitations of the Census Bureau Methodology Ranking Racial and Ethnic Residential Segregation in Cities and Metro Areas - (:unkn) unknown (My University, 2005)
This paper responds to a request from the U.S. Census Bureau to serve on a five-member peer review panel to examine an historic and first-time study by the Census Bureau that ranked major metropolitan areas by their level of racial and ethnic housing segregation and offered segregation rankings of 1,092 cities and 331 metropolitan areas based on a series of indexes discussed in the sociological literature. The paper identifies assumptions and limitations of the indexes and the five-index rankings used by the Census Bureau in its report on “Racial and Ethnic Residential Segregation in the United States: 1980-2000” (CENSR-3) and its “Segregation / Housing Pattern Index Tables” posted on the Census Bureau website, and questions the appropriateness of the Census Bureau promoting schemes for ranking cities and metropolitan areas on their population distributions.
Keywords: U.S. Census; housing segregation; housing integration